Contribution of Thyrotropin-Releasing Hormone to Cerebellar Long-Term Depression and Motor Learning - Watanave, Masashi; Matsuzaki, Yasunori; Nakajima, Yasuyo; Ozawa, Atsushi; Yamada, Masanobu; Hirai, Hirokazu (Frontiers in Cellular Neuroscience, 2018)
Thyrotropin-releasing hormone (TRH) regulates various physiological activities through activation of receptors expressed in a broad range of cells in the central nervous system. The cerebellum expresses TRH receptors in granule cells and molecular layer interneurons. However, the function of TRH in the cerebellum remains to be clarified. Here, using TRH knockout (KO) mice we studied the role of TRH in the cerebellum. Immunohistochemistry showed no gross morphological differences between KO mice and wild-type (WT) littermates in the cerebellum. In the rotarod test, the initial performance of KO mice was comparable to that of WT littermates, but the learning speed of KO mice was significantly lower than that of WT littermates, suggesting impaired motor learning. The motor learning deficit in KO mice was rescued by intraperitoneal injection of TRH. Electrophysiology revealed absence of long-term depression (LTD) at parallel fiber-Purkinje cell synapses in KO mice, which was rescued by bath-application of TRH. TRH was shown to increase cyclic guanosine monophosphate (cGMP) content in the cerebellum. Since nitric oxide (NO) stimulates cGMP synthesis in the cerebellum, we examined whether NO-cGMP pathway was involved in TRH-mediated LTD rescue in KO mice. Pharmacological blockade of NO synthase and subsequent cGMP production prevented TRH-induced LTD expression in KO mice, whereas increase in cGMP signal in Purkinje cells by 8-bromoguanosine cyclic 3',5'-monophosphate, a membrane-permeable cGMP analog, restored LTD without TRH application. These results suggest that TRH is involved in cerebellar LTD presumably by upregulating the basal cGMP level in Purkinje cells, and, consequently, in motor learning.